A comprehensive review on the advances of bioproducts from biomass towards meeting net zero carbon emissions (NZCE). (December 2022) - Tijjani Usman, Ibrahim Muntaqa; Ho, Yeek-Chia; Baloo, Lavania; Lam, Man-Kee; Sujarwo, Wawan
Graphical abstract: Highlight: Various materials and mechanisms for bioproduct as feedstock for NZCE. Intriguing use in water treatment and renewable energy. Futuristic insight on the NCZE on carbon dioxide. Abstract: This review investigates the development of bioproducts from biomass and their contribution towards net zero carbon emissions. The promising future of biomasses conversion techniques to produce bioproducts was reviewed. The advances in anaerobic digestion as a biochemical conversion technique have been critically studied and contribute towards carbon emissions mitigation. Different applications of microalgae biomass towards carbon neutrality were comprehensively discussed, and several research findings have been tabulated in this review. The carbon footprints of wastewater treatment plants were studied, and bioenergy utilisation from sludge production was shown to mitigate carbon footprints. The carbon-sinking capability of microalgae has also been outlined. Furthermore, integrated conversion processes have shown to enhance bioproducts generation yield and quality. The anaerobic digestion/pyrolysis integrated process was promising, and potential substrates have been suggested for future research. Lastly, challenges and future perspectives of bioproducts were outlined for a contribution towards meeting carbon neutrality.